Catalyst for reducing generation amount of N2O in ammonia gas conversion process and preparation method thereof

By designing the inner ammonia adsorption conversion functional coating and the outer NO reduction functional coating in the catalyst, the problems of low NOx conversion efficiency and high N2O generation at low temperatures are solved, and the effects of low cost and low N2O emissions are achieved. Avoid the use of precious metals.

CN119114150AActive Publication Date: 2024-12-13WUXI WEIFU ENVIRONMENT PROTECTION CATALYST

Patent Information

Application Number
CN202411483218.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2024-12-13
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The existing NH3-SCR catalysts have low NOx conversion efficiency at low temperatures, resulting in high ammonia injection and N2O generation, and high precious metal usage leads to cost pressure, making it difficult to meet future regulations and cost reduction requirements.

Method used

A catalyst is designed including an inner layer of ammonia adsorption conversion functional coating and an outer layer of NO reduction functional coating. The inner layer of ammonia adsorbs excessive ammonia at low temperature, converts it to NO as the temperature increases, and is coated through the outer layer. The layer reacts with ammonia to produce N2 and H2O, reducing the amount of N2O generation, and no precious metals such as Pt are used.

Benefits of technology

The NOx conversion efficiency at low temperatures is improved, the N2O generation amount is reduced, and the production cost of catalysts is reduced, achieving a balance between low N2O emissions and cost-effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114150A_ABST
    Figure CN119114150A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalyst preparation, and particularly relates to a catalyst for reducing the generation amount of N2O in an ammonia gas conversion process and a preparation method of the catalyst. The catalyst comprises a carrier, wherein the carrier is sequentially coated with an ammonia gas adsorption and conversion functional coating and an NO reduction functional coating; the NO reduction functional coating comprises a first molecular sieve and Cu or Fe, and further comprises a pore-forming template agent, and Cu or Fe is loaded on the first molecular sieve; the ammonia gas adsorption and conversion functional coating comprises a second molecular sieve and active metal. The inner-layer ammonia gas adsorption and conversion functional coating of the catalyst can adsorb excessive ammonia gas jetted from the upstream at low temperature, the ammonia gas conversion capacity is improved along with temperature rise, the ammonia gas is converted into NO, and the formed NO is rapidly diffused to the outer-layer NO reduction functional coating and reacts with the ammonia gas adsorbed by the outer-layer NO reduction functional coating to generate N2 and H2O. Over-oxidation of ammonia gas is effectively reduced, and the generation amount of N2O is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalyst preparation, and in particular relates to a catalyst for reducing the amount of N2O generated in an ammonia conversion process and a preparation method thereof. Background Art

[0002] NH3-SCR technology catalyst used in lean-burn engine aftertreatment can effectively solve the problem of nitrogen oxides (NO x ) emission problem and achieve the engineering target value. However, in practical applications, because the catalyst under low temperature conditions (<250℃) does not reach the optimal working area, NO x The conversion efficiency is low (<90%), as reported by Kwak JH et al. [1] . In order to achieve the nitrogen oxide emission target, the system will over-inject ammonia, resulting in ammonia leakage problems. The function of the ammonia conversion catalyst in the after-treatment system is to convert the over-injected ammonia into N2. At present, the active metal in the catalyst that oxidizes ammonia is Pt. Because of its relatively high activity, ammonia will be over-oxidized during the catalytic process, resulting in the inevitable production of a large amount of N2O. With the increasingly stringent regulations in the future, especially the limit requirements for N2O, the existing catalyst solutions face huge challenges. In addition, with the cost reduction requirements of upstream vehicles, catalyst companies are also facing huge cost reduction pressure, and the precious metals in the catalyst have become the first choice for cost reduction for various manufacturers due to their high prices. However, while achieving the function and efficiency of the catalyst, how to reduce the use of precious metals is also a challenge faced by after-treatment companies. In response to the above challenges, how to optimize the ammonia conversion catalyst unit module to achieve low N2O emissions and cost reduction needs is an urgent problem that all after-treatment catalyst manufacturers need to solve.

[0003] References: [1]Kwak JH, Tran D, Burton SD, et al. Effects ofhydrothermal aging on NH3-SCR reaction over Cu / zeolites[J].Journal ofCatalysis, 2012, 287(none):203-209.DOI:10.1016 / j.jcat.2011.12.025. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a catalyst for reducing the amount of N2O generated during ammonia conversion and a preparation method thereof. The catalyst of the present invention includes a carrier and an inner ammonia adsorption conversion functional coating and an outer NO reduction functional coating sequentially coated on the carrier. The inner ammonia adsorption conversion functional coating can adsorb excess ammonia injected upstream at low temperatures. As the temperature rises, the ammonia conversion capacity increases, converting ammonia into NO. The formed NO quickly diffuses to the outer NO reduction functional coating, reacts with ammonia adsorbed by the outer NO reduction functional coating to generate N2 and H2O, effectively reducing excessive oxidation of ammonia and reducing the amount of N2O generated.

[0005] In order to achieve the above technical objectives, the technical solution adopted by the embodiment of the present invention is: In a first aspect, an embodiment of the present invention provides a catalyst for reducing the amount of N2O generated during ammonia conversion, including a carrier, on which an ammonia adsorption conversion functional coating and a NO reduction functional coating are sequentially coated; The NO reduction functional coating comprises a first molecular sieve and Cu or Fe, and also comprises a pore-forming template, wherein the Cu or Fe is loaded on the first molecular sieve; The ammonia adsorption and conversion functional coating comprises a second molecular sieve and an active metal.

[0006] Furthermore, the first molecular sieve loaded with Cu or Fe is one or more of SSZ-13, SSZ-16, SSZ-39, SSZ-52, SSZ-98, ZK-4, ZK-5, ZK-20, ZK-22, ZSM-5, ZSM-35, ZSM-58, MOR and BETA.

[0007] Furthermore, the second molecular sieve is one or more of SSZ-13, SSZ-16, SSZ-39, SSZ-52, SSZ-98, ZK-4, ZK-5, ZK-20, ZK-22, ZSM-5, ZSM-35, ZSM-58, MOR, and BETA.

[0008] Furthermore, the active metal is one or more of Cu, Fe, Mn, Ce, Zr, La, Al, Y, Nd and Hf.

[0009] Furthermore, in the ammonia adsorption and conversion functional coating, the active metal is physically mixed with the second molecular sieve in the form of an oxide, or the active metal is loaded in the second molecular sieve in an ionic state.

[0010] Furthermore, the loading amount of the NO reduction functional coating on the carrier is 80-200 g / L, and the loading amount of the ammonia adsorption conversion functional coating on the carrier is 40-100 g / L.

[0011] Furthermore, the weight proportion of the second molecular sieve in the ammonia adsorption conversion functional coating is 10%-50%.

[0012] Furthermore, in the NO reduction functional coating, the weight proportion of Cu or Fe is 1%-5%.

[0013] Furthermore, the pore-forming template agent includes one or more of starch, polydextrose, carboxymethyl cellulose, hydroxyethyl cellulose, polyethylene, polypropylene, polyimide and polyvinyl alcohol fiber, and the added amount is 0.5wt%-1wt% of the weight of the NO reduction functional coating.

[0014] In a second aspect, an embodiment of the present invention provides a method for preparing the catalyst according to the first aspect, comprising the following steps: (1) Coating of the inner layer ammonia adsorption and conversion functional coating: coating the prepared ammonia adsorption and conversion functional coating slurry on the carrier, drying at 120-150°C for 1-2 hours, and calcining at 500-550°C for 1-2 hours to obtain a semi-finished catalyst A for standby use; (2) Coating of the outer NO reduction functional coating: Prepare a suspension of the first molecular sieve loaded with Cu or Fe, add aluminum sol and stir evenly, then add a pore-forming template agent to the suspension, and then coat it on the semi-finished catalyst A obtained in step (1) according to the loading amount requirement, dry it at 120-150°C for 1-2h, and calcine it at 500-550°C for 1-2h to obtain a finished catalyst; The ammonia adsorption conversion functional coating slurry is prepared by one of the following methods: a. Physically mix the active metal with the molecular sieve in the form of oxide: add the active metal in the form of oxide to the second molecular sieve suspension, add aluminum sol after mixing and stir evenly; b. Active metals are loaded in the molecular sieve in ionic form: the second molecular sieve is calcined at 300-350°C for 0.5-1h, placed in a dryer and cooled to room temperature, the active metal is added to the uniformly stirred second molecular sieve powder in the form of an ionic salt solution, and after standing for 12-24h, the powder is dried in a microwave at 120-150°C for 0.5-1h, and the dried powder is prepared into a suspension and aluminum sol is added and stirred evenly.

[0015] The technical solution in the embodiment of the present invention has the following beneficial effects: The present invention optimizes the catalyst composition and adds a second molecular sieve to the inner ammonia adsorption and conversion functional coating to increase the ammonia adsorption capacity at low temperatures, effectively alleviating the NO in the NH3-SCR process at low temperatures. xThe conversion efficiency is too low, and the SCR system over-injects ammonia, causing leakage. At the same time, adding a template agent to the outer NO reduction functional coating increases the porosity of the outer coating, which is not only conducive to the inward transmission of ammonia, but also conducive to the inner layer converting ammonia into NO x It is quickly transferred to the outer layer and reacts with the ammonia adsorbed in the outer layer, and at the same time, the amount of N2O generated is reduced during the ammonia conversion process. In addition, the present invention does not use precious metals such as Pt, Pd, and Rh, which can reduce the cost of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a curve diagram of the change of ammonia adsorption capacity of the catalyst in Example 1 and Comparative Example 1.

[0017] Figure 2 It is the change curve of ammonia concentration in the tail gas of the ammonia conversion performance evaluation in Example 1 and Comparative Example 1.

[0018] Figure 3 It is a curve chart showing the change in the amount of N2O generated during the ammonia conversion process of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0020] The carriers used to prepare the catalysts in Examples 1-3 and Comparative Example 1 were all ceramic honeycomb carriers with a size of 143.8 mm×101.6 mm and a mesh size of 400 meshes.

[0021] Example 1 A method for preparing a catalyst for reducing the amount of N2O generated during ammonia conversion, comprising the following steps: (1) Coating of the inner layer ammonia adsorption and conversion functional coating: MnO2, CeO2, and ZrO2 were added to the SSZ-13 molecular sieve suspension (wherein the SSZ-13 molecular sieve accounted for 10% of the total weight of the coating) at a molar ratio of Mn:Ce:Zr of 0.5:1:4, and after mixing, 1wt% aluminum sol (based on the mass of alumina) was added and stirred for 1 hour. The above suspension was coated on the honeycomb carrier at a loading amount of 40g / L, dried at 120°C for 2h, and calcined at 500°C for 1h to obtain a semi-finished catalyst A for standby use; (2) Coating of the outer NO reduction functional coating: Prepare a suspension of SSZ-13 molecular sieve material loaded with 3 wt% Cu, add 1 wt% aluminum sol (based on the mass of alumina) and stir for 1 h. Then add 1% polydextrose by weight of the coating to the suspension, and then coat it on the semi-finished catalyst A at a loading amount of 120 g / L. Dry at 120 °C for 2 h and calcine at 500 °C for 1 h to obtain a finished catalyst.

[0022] Example 2 A method for preparing a catalyst for reducing the amount of N2O generated during ammonia conversion, comprising the following steps: (1) Coating of the inner layer ammonia adsorption and conversion functional coating: SSZ-13 molecular sieve loaded with 5wt% Cu was calcined at 300°C for 1h, placed in a dryer and cooled to room temperature, and manganese nitrate, cerium nitrate and zirconium nitrate were added to the uniformly stirred Cu-SSZ-13 molecular sieve powder in the form of ionic salt solutions according to the molar ratio of Mn:Ce:Zr of 0.5:1:4 (wherein the SSZ-13 molecular sieve accounts for 30% of the total weight of the coating), and after standing for 12h, the powder was dried at 150°C for 0.5h in a microwave oven, and the dried powder was prepared into a suspension, and 1wt% aluminum sol (based on the mass of alumina) was added and stirred for 1h. The suspension was coated on a honeycomb carrier at a loading of 100g / L, dried at 120°C for 2h, and calcined at 500°C for 1h to obtain a semi-finished catalyst A for standby use; (2) Coating of the outer NO reduction functional coating: Prepare a suspension of BETA molecular sieve material loaded with 1 wt% Fe, add 1 wt% aluminum sol (calculated as alumina mass) and stir for 1 h. Then add 1% carboxymethyl cellulose (based on the weight of the coating) to the suspension, and then coat it on the semi-finished catalyst A at a loading amount of 80 g / L. Dry at 120°C for 2 h and calcine at 500°C for 1 h to obtain a finished catalyst.

[0023] Example 3 A method for preparing a catalyst for reducing the amount of N2O generated during ammonia conversion, comprising the following steps: (1) Coating of the inner layer ammonia adsorption and conversion functional coating: calcine a ZSM-5 molecular sieve loaded with 10 wt% Cu at 300°C for 1 h, place it in a dryer and cool it to room temperature, add aluminum nitrate, cerium nitrate and zirconium nitrate in the form of an ionic salt solution at a molar ratio of Al:Ce:Zr of 2:1:2 to the uniformly stirred Cu-ZSM-5 molecular sieve powder (wherein the ZSM-5 molecular sieve accounts for 50% of the total weight of the coating), let it stand for 12 h, and then dry it at 150°C for 0.5 h in a microwave oven, prepare the dried powder into a suspension, add 1 wt% aluminum sol (based on the mass of alumina) and stir for 1 h, and coat the suspension on a honeycomb carrier at a loading of 80 g / L, dry it at 120°C for 2 h, and calcine it at 500°C for 1 h to obtain a semi-finished catalyst A for standby use; (2) Coating of the outer NO reduction functional coating: Prepare a suspension of BETA molecular sieve material loaded with 5 wt% Cu, add 1 wt% aluminum sol (based on the mass of alumina) and stir for 1 h. Then add 1% hydroxyethyl cellulose (based on the weight of the coating) to the suspension, and then coat it on the semi-finished catalyst A at a loading amount of 200 g / L. Dry at 120°C for 2 h and calcine at 500°C for 1 h to obtain a finished catalyst.

[0024] Comparative Example 1 (1) Inner layer coating: add 3 g / ft³ of Pt to the alumina suspension, then add 1 wt% of aluminum sol (based on the mass of alumina) and stir for 1 h. Apply the suspension to the honeycomb carrier at a loading amount of 40 g / L, dry at 120°C for 2 h, and calcine at 500°C for 1 h to obtain a semi-finished catalyst A for standby use. (2) Outer layer coating: Prepare a suspension of SSZ-13 molecular sieve material loaded with 3 wt% Cu, add 1 wt% aluminum sol (based on the mass of alumina) and stir for 1 h. Then add 1% of the coating weight of polydextrose to the suspension, and then coat it on the semi-finished catalyst A at a loading amount of 120 g / L. Dry at 120°C for 2 h and calcine at 500°C for 1 h to obtain a traditional precious metal-based finished catalyst.

[0025] Catalyst NOx conversion performance evaluation: The experiment used a fixed bed microreactor to load the sample and the exhaust gas components were detected by a MKS2030 Fourier transform infrared analyzer. The experimental conditions were: space velocity 60000 h -1 , NO 500ppm, NH3500ppm, 14%O2, 5% H2O, and N2 as balance gases.

[0026] Catalyst ammonia conversion performance evaluation: The experiment used a fixed bed microreactor to load the sample and test the tail gas components using a MKS2030 Fourier transform infrared analyzer. The experimental conditions were: space velocity 60000 h -1, NO 150ppm, NH3450ppm, 14%O2, 5% H2O, and N2 as the balance gas.

[0027] Ammonia adsorption performance of catalyst coating: The experiment was carried out using a fixed bed microreactor for sample loading and testing, and the tail gas components were detected using a MKS2030 Fourier transform infrared analyzer. The experimental conditions were: space velocity 60000 h -1 , 500ppm NH3, 5% H2O, and N2 were used as the balance gases.

[0028] Figure 1 The curve diagram of the ammonia adsorption storage capacity of the catalyst coating is shown in Figure 1. Since the outer coating of the catalyst in Example 1 and Comparative Example 1 is the same, the difference in ammonia adsorption storage capacity is caused by the difference in the inner coating. Figure 1 It can be seen that the inner coating of Comparative Example 1 has almost no ammonia adsorption and storage capacity, while the catalyst of Example 1 has a higher ammonia adsorption amount, and the ammonia adsorption amount decreases with increasing temperature.

[0029] Figure 2 : is the curve of the change of ammonia concentration in the tail gas during the ammonia conversion performance evaluation experiment. It can be seen from the figure that the ammonia concentration in the tail gas of Example 1 and Comparative Example 1 both decreases with the increase of temperature. However, in the range of 150-265°C, the ammonia concentration of Example 1 is significantly less than that of Comparative Example 1. The decrease in ammonia concentration in Example 1 is mainly due to the ammonia adsorption and conversion function of the inner coating at low temperatures. Since the inner coating of the catalyst in Comparative Example 1 has almost no ammonia adsorption and storage capacity, the decrease in ammonia concentration in Comparative Example 1 is mainly due to the adsorption of the outer layer and the conversion reaction of the inner layer. When the temperature is greater than 265°C, the ammonia concentration in Example 1 is slightly greater than that in Comparative Example 1, mainly because the inner coating of the catalyst in Comparative Example 1 uses the precious metal Pt to exhibit excellent ammonia conversion ability.

[0030] Figure 3 3 is a curve of N2O concentration change in tail gas during the ammonia conversion evaluation experiment. It can be seen from the figure that both catalysts produce different amounts of N2O. The N2O generation of Example 1 reaches a peak at around 300°C, and the N2O generation of Comparative Example 1 reaches a peak at around 250°C. The peak concentration of Example 1 is about 40ppm lower than that of Comparative Example 1, and the total amount of N2O generated in the entire temperature window is about 13.5% lower.

[0031] In summary, the inner ammonia adsorption and conversion functional coating of the catalyst of the present invention can adsorb excess ammonia injected upstream at low temperatures. As the temperature rises, the ammonia conversion capacity increases, and the ammonia is converted into NO. The formed NO quickly diffuses to the outer NO reduction functional coating, and reacts with the ammonia adsorbed by the outer NO reduction functional coating to generate N2 and H2O, effectively reducing excessive oxidation of ammonia and reducing the amount of N2O generated. In addition, the catalyst of the present invention does not use precious metals including Pt, which can greatly reduce the production cost of the catalyst.

[0032] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A catalyst for reducing the amount of N2O generated during ammonia conversion, characterized in that: The method comprises a carrier, on which an ammonia adsorption and conversion functional coating and a NO reduction functional coating are sequentially coated; The NO reduction functional coating comprises a first molecular sieve and Cu or Fe, and also comprises a pore-forming template, wherein the Cu or Fe is loaded on the first molecular sieve; The ammonia adsorption and conversion functional coating comprises a second molecular sieve and an active metal.

2. The catalyst for reducing the amount of N2O generated during ammonia conversion according to claim 1, characterized in that: The first molecular sieve loaded with Cu or Fe is one or more of SSZ-13, SSZ-16, SSZ-39, SSZ-52, SSZ-98, ZK-4, ZK-5, ZK-20, ZK-22, ZSM-5, ZSM-35, ZSM-58, MOR and BETA.

3. The catalyst for reducing the amount of N2O generated during ammonia conversion according to claim 1, characterized in that: The second molecular sieve is one or more of SSZ-13, SSZ-16, SSZ-39, SSZ-52, SSZ-98, ZK-4, ZK-5, ZK-20, ZK-22, ZSM-5, ZSM-35, ZSM-58, MOR, and BETA.

4. The catalyst for reducing the amount of N2O generated during ammonia conversion according to claim 1, characterized in that: The active metal is one or more of Cu, Fe, Mn, Ce, Zr, La, Al, Y, Nd and Hf.

5. The catalyst for reducing the amount of N2O generated during ammonia conversion according to claim 1, characterized in that: In the ammonia adsorption and conversion functional coating, the active metal is physically mixed with the second molecular sieve in the form of oxide, or the active metal is loaded in the second molecular sieve in the form of ions.

6. The catalyst for reducing the amount of N2O generated during ammonia conversion according to claim 1, characterized in that: The loading amount of the NO reduction functional coating on the carrier is 80-200 g / L, and the loading amount of the ammonia adsorption conversion functional coating on the carrier is 40-100 g / L.

7. The catalyst for reducing the amount of N2O generated during ammonia conversion according to claim 1, characterized in that: The weight proportion of the second molecular sieve in the ammonia adsorption conversion functional coating is 10%-50%.

8. The catalyst for reducing the amount of N2O generated during ammonia conversion according to claim 1, characterized in that: In the NO reduction functional coating, the weight proportion of Cu or Fe is 1%-5%.

9. The catalyst for reducing the amount of N2O generated during ammonia conversion according to claim 1, characterized in that: The pore-forming template agent includes one or more of starch, polydextrose, carboxymethyl cellulose, hydroxyethyl cellulose, polyethylene, polypropylene, polyimide and polyvinyl alcohol fiber, and the added amount is 0.5wt%-1wt% of the weight of the NO reduction functional coating.

10. The method for preparing the catalyst according to any one of claims 1 to 9, characterized in that: The steps include: (1) Coating of the inner layer ammonia adsorption and conversion functional coating: coating the prepared ammonia adsorption and conversion functional coating slurry on the carrier, drying at 120-150°C for 1-2 hours, and calcining at 500-550°C for 1-2 hours to obtain a semi-finished catalyst A for standby use; (2) Coating of the outer NO reduction functional coating: Prepare a suspension of the first molecular sieve loaded with Cu or Fe, add aluminum sol and stir evenly, then add a pore-forming template agent to the suspension, and then coat it on the semi-finished catalyst A obtained in step (1) according to the loading amount requirement, dry it at 120-150°C for 1-2h, and calcine it at 500-550°C for 1-2h to obtain a finished catalyst; The ammonia adsorption conversion functional coating slurry is prepared by one of the following methods: a. Physically mix the active metal with the molecular sieve in the form of oxide: add the active metal in the form of oxide to the second molecular sieve suspension, add aluminum sol after mixing and stir evenly; b. Active metals are loaded in the molecular sieve in ionic form: the second molecular sieve is calcined at 300-350°C for 0.5-1h, placed in a dryer and cooled to room temperature, the active metal is added to the uniformly stirred second molecular sieve powder in the form of an ionic salt solution, and after standing for 12-24h, the powder is dried in a microwave at 120-150°C for 0.5-1h, and the dried powder is prepared into a suspension and aluminum sol is added and stirred evenly.

Citation Information

Patent Citations

  • Hydrogen internal combustion engine catalyst and preparation method thereof

    CN115400787A

  • SCR (Selective Catalytic Reduction) catalyst with low N2O generation amount and preparation method thereof

    CN117299196A

  • Sectional catalyst for treating N2O in vehicle tail gas and preparation method

    CN117797860A

  • Coupling type three-way catalyst for diesel engine and preparation method of coupling type three-way catalyst

    CN118002195A

  • Low-temperature ammoxidation ASC catalyst for diesel engine

    CN118477680A

Cited By

  • Device system and method for cooperative control of boiler ammonia escape and NOx and product treatment

    CN121025482A

  • Multi-element gas adsorbent as well as preparation method and application thereof

    CN121534677A